Enhanced benthic nitrous oxide and ammonium production after natural oxygenation of long‐term anoxic sediments - Processes and pools in the benthic nitrogen cycle after natural oxygenation of long-term anoxic sediment - Hylén, Astrid; Bonaglia, Stefano; Robertson, Elizabeth; Marzocchi, Ugo; Kononets, Mikhail; Hall, Per (University of Gothenburg, 2022)
In this study, we describe the long-term impact of a natural oxygenation event on the fate of fixed nitrogen in the sediment. We investigated whether the newly oxygenated sediments were sites of efficient removal of fixed nitrogen through denitrification and anammox, which environmental factors affected the division between nitrate reduction processes, and whether nitrate from the water column or sedimentary nitrification was fuelling nitrate reduction processes in the sediment. We conducted three yearly samplings in 2016, 2017, and 2018, where we performed in situ measurements of nitrate reduction process rates and sediment–water fluxes of nutrients, oxygen and dissolved inorganic carbon . We additionally collected sediment samples and measured sediment microprofiles of oxygen, nitrous oxide and hydrogen sulphide to gain further insights into the spatial distribution of the processes in surface sediments.

The data set contains 5 files with the following data:

- Station information; locations, sediment surface and bottom water conditions
- Sediment properties; carbon and nitrogen in the sediment solid phase, porosity, pore water concentrations of NOx and NH4.
- Microsensor measurements of O2, N2O and H2S
- Sediment-water fluxes of oxygen, dissolved inorganic carbon, NH4 and NOx
- Nitrate reduction rates in the sediment

Full descriptions of the data can be found in the corresponding readme files accessible from the Data and documentation tab.

Studiens mål var att utvärdera hur ett syresatt vatteninflöde till de djupa delarna av Östersjön påverkade kvävecykeln i tidigare långtidsanoxiska sediment. Se utförlig beskrivning i den engelska versionen av katalogposten.

Datasetet innehåller 5 filer med följande data:
- Stationsinformation; koordinater, kemisk information om sedimentytan och bottenvattnet
- Sedimentegenskaper; kol och kväve i sedimentets fasta fas, porositet, koncentrationer av NOx och NH4 i porvattnet
- Mikrosensormätningar av O2, N2O och H2S
- Sediment-vattenflöden av syre, löst oorganiskt kol, NH4 och NOx
- Nitratreduktionshastigheter i sedimentet

Utförlig beskrivning av data finns i de tillhörande readme-filerna under fliken Data och dokumentation.
Ökad bentisk produktion av kvävedioxid och ammonium efter naturlig syresättning av långtidsanoxiska sediment - Processer och pooler i den bentiska kvävecykeln efter naturlig syresättning av långtidsanoxiskt sediment
Keywords: SEDIMENT COMPOSITION; SEDIMENT CHEMISTRY; marine sediment; mud (sediment); mudder; sediment; sediment; biogeochemical process; nitrogen retention; nitrogen removal; nitrogen metabolism; ammonium nitrogen compounds; organic matter; organiskt material; nitrogen-15; dissolved inorganic nitrogen; nitrogen cycle; kvävets kretslopp; oxygen consumption; sediment organic content proportion; nitrogen-15 method; sediment chemistry; dissolved oxygen; upplöst syre; nitrogen dioxide; sediment content; sediment oxygen demand; marine sediment; Geochemistry; Geokemi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Environmental Management; Miljöteknik och miljöledning